Вплив атмосфери на послаблення лазерного променя при скануванні місцевості - Бурштинська, Х. В.; Бабушка, А. В. (Видавництво Львівської політехніки, 2013)
Рассмотрены факторы, влияющие на ослабление лазерного излучения в атмосфере. Рассчитаны коэффициенты аэрозольного ослабления и коэффициенты молекулярного рассеяния лазерного сигнала. The factors affecting the attenuation of laser radiation in the atmosphere are considered. The coefficients of the aerosol extinction and coefficients molecular scattering of the laser signal are calculated.